The Use Of Game-Based Learning In Enriching The Arabic Vocabulary Of Religious Secondary School Students In Malaysia - Muhammad Hafiz Bukhari Mohd Khadari; Wan Suraya Wan Nik; Nursyahidah Khalid (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Game-Based Learning (GBL) is an educational approach that uses games as the basis of an interactive medium to increase student motivation and engagement in an immersive way. In general, GBL is divided into two main forms, namely digital-based games such as social media applications and Artificial Intelligence (AI)-based platforms, and physical games such as crossword puzzles and flashcards. The development of AI technology after the COVID-19 pandemic has led to the emergence of various exciting innovations in education, including the integration of GBL in Arabic language learning. However, traditional methods based on memorization and repetition are becoming less relevant because they have the potential to affect student motivation and engagement. In addition, the issue of students' lack of interest in Arabic due to factors other than native speakers has become a point of difficulty for Arabic language teachers. Arabic language teachers also face difficulties in helping students remember and understand words, causing students to be at an unsatisfactory level. Therefore, this study aims to explore the challenges of lower secondary students towards the use of AI-based GBL in Arabic vocabulary learning, in addition to identifying their needs and perceptions of this approach. This study used a phenomenological qualitative design with face-to-face interview techniques, structured observation through test questions, small group discussions, and document analysis. Data were analyzed thematically to produce a comprehensive picture of the students' experiences. The target sample respondents consisted of Form 2 and Form 3 students at Sekolah Menengah Agama Negeri (SMAN) Perak. The study findings are expected to provide an in-depth picture of the potential and effectiveness of GBL in enriching Arabic vocabulary which contributes to strengthening language literacy through the use of AI technology.Keywords: Game-Based Learning, Artificial Intelligence, Arabic vocabulary, innovation, challenges